Dalit responses to unemployment in contemporary India - Marika Vicziany (South Asia: Journal of South Asian Studies, n.s., Vol.XXVIII, no.1, April, 2005, 2005)
Given the rapid rise of unemployment in India, how is this affecting the new generation of college-educated dalits? An earlier paper described the current generation of college-educated dalit students as the `breakthrough generation', because their numbers and educational achievements mark a distinctive break with the past.1 The present paper looks at dalit responses to unemployment. Specifically it examines three different kinds of responses by urban dalits in western India, using in-depth case studies of some young dalit lives. The aspirations of college-educated dalit students are linked to evidence about the rising unemployment in India during the 1990s, and the consequences of the extreme socio-economic pressures that this has exerted on one of India's most significant minorities, currently numbering in excess of 150 million people. The chief causes of unemployment are examined, together with the arguments for affirmative action in the corporate sector. The paper concludes by considering how mass unemployment, especially amongst educated dalits, increases the ability of the sangh parivar2 to recruit young supporters to the cause of Hindu militancy.